2012
DOI: 10.1016/j.jacc.2011.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dyspnea in Acute Decompensated Heart Failure

Abstract: PEFR increases over the first 24 h in AHF and could serve as an AHF endpoint. Nesiritide had a greater effect than placebo on PEFR, and this predicted patients with moderate/marked improvement in dyspnea, thereby providing an objective metric for assessing AHF. (Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure [ASCEND-HF]; NCT00475852).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Previous studies explored associations between objective measures of dyspnea evaluation (eg, peak expiratory flow rate) and patient-reported measures of dyspnea by Likert scale. 19 To our knowledge, no study has demonstrated that objective measures of dyspnea at baseline adequately quantify patient-reported dyspnea severity on admission. These data in combination with our analysis support the utility of assessing patient-reported dyspnea severity on admission for acute HF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies explored associations between objective measures of dyspnea evaluation (eg, peak expiratory flow rate) and patient-reported measures of dyspnea by Likert scale. 19 To our knowledge, no study has demonstrated that objective measures of dyspnea at baseline adequately quantify patient-reported dyspnea severity on admission. These data in combination with our analysis support the utility of assessing patient-reported dyspnea severity on admission for acute HF.…”
Section: Discussionmentioning
confidence: 99%
“…(95,96) Assessment of dyspnea is not only plagued by its difficult recognition but also by its lack of an objective gold standard for validation. (97,98) Studies have repeatedly failed to link patient-reported dyspnea to objective measurements such as pulmonary-capillary wedge pressure, left ventricular ejection fraction, and cardiac output. (18,31,99) Similarly, dyspnea does not correlate well with spirometry or pulse oximetry, though one trial suggested that the use of peak expiratory flow rate may be helpful.…”
Section: Dyspneamentioning
confidence: 99%
“…Moreover, dyspnea correlates poorly with in-hospital worsening HF and postdischarge events (e.g., readmission and mortality) making it difficult to rely on as the sole measure of improvement. 126129 Maneuvers that illicit cardiac stress through provocation with position change (i.e., seated to supine) or physical exertion (i.e., walk tests) may help delineate more subtle effects of AHF on dyspnea and thus serve as more definitive measures of clinical improvement, but have yet to be tested in prospective trials. 130 Further, other HF symptoms, such as fatigue and body swelling, may be as meaningful as dyspnea to patients and important patient-centered endpoints to explore.…”
Section: Unanswered Questions and Future Research Agendamentioning
confidence: 99%